The Effect Jicama Flour Substitution On The Quality Of Coconut Root Cake - Susanti, Hafifah Mardiah; Gusnita, Wiwik; Holinesti, Rahmi; Siregar, Juliana (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
Coconut root dry cakes or cactus cakes are dry cakes made from white glutinous rice flour, coconut milk, sugar and eggs which are stirred together then fried using a tool by pressing or turning a lever where the spuid is directed into medium hot oil, then the mixture is fried until ripe. This research is motivated by the use of local food ingredients, namely jicama, which is still lacking. Jicama is made into flour to be varied into one of the pastries, namely coconut root cake. The aim of this research was to analyze the effect of 0%, 15%, 30% and 45% substitution of jicama flour on the quality of coconut root cake in terms of shape, color, aroma, texture and taste. This type of research is a pure experiment using a completely randomized design (CRD) method and three repetitions. The data source in this research was obtained from 3 limited expert panelists, namely lecturers at the Department of Family Welfare Science, Culinary Education Concentration, Faculty of Tourism and Hospitality, Padang State University. The tool used to collect data was a questionnaire containing questions regarding the quality of coconut root cake. Data were analyzed using ANOVA, if Fcount≥Ftable then continued with the Duncan Test. The results of this research show that there is a real influence on the quality of color and texture of coconut root cake, while there is no significant difference in the quality of shape, aroma and taste. It can be concluded that the best quality test results for coconut root cake were in treatment X1 with 15% jicama flour substitution.